Mechanisms of ubiquitin-independent proteasomal degradation and their roles in age-related neurodegenerative disease - Church, Taylor R.; Margolis, Seth S. (Frontiers in Cell and Developmental Biology, 2025)
Neurodegenerative diseases are characterized by the progressive breakdown of neuronal structure and function and the pathological accumulation of misfolded protein aggregates and toxic protein oligomers. A major contributor to the deterioration of neuronal physiology is the disruption of protein catabolic pathways mediated by the proteasome, a large protease complex responsible for most cellular protein degradation. Previously, it was believed that proteolysis by the proteasome required tagging of protein targets with polyubiquitin chains, a pathway called the ubiquitin-proteasome system (UPS). Because of this, most research on proteasomal roles in neurodegeneration has historically focused on the UPS. However, additional ubiquitin-independent pathways and their importance in neurodegeneration are increasingly recognized. In this review, we discuss the range of ubiquitin-independent proteasome pathways, focusing on substrate identification and targeting, regulatory molecules and adaptors, proteasome activators and alternative caps, and diverse proteasome complexes including the 20S proteasome, the neuronal membrane proteasome, the immunoproteasome, extracellular proteasomes, and hybrid proteasomes. These pathways are further discussed in the context of aging, oxidative stress, protein aggregation, and age-associated neurodegenerative diseases, with a special focus on Alzheimer’s Disease, Huntington’s Disease, and Parkinson’s Disease. A mechanistic understanding of ubiquitin-independent proteasome function and regulation in neurodegeneration is critical for the development of therapies to treat these devastating conditions. This review summarizes the current state of ubiquitin-independent proteasome research in neurodegeneration.